THE EFFECT OF USING LEARNING MEDIA ON LEARNING INTERESTS OF GRADE V STUDENTS OF SDN 127 INPRES MONCONGLOE MAROS - Muhammad Irsandi Irwan; Mustafa; Widya Karmila Sari Achmad (Media Inovasi Pendidikan dan Publikasi, 2024)
The formulation of the problem in this study is how is the description of learning interest, the use of learning media of class V students of SDN 127 Inpres Moncongloe before and after using powtoon learning media? and is there a significant influence of the use of powtoon learning media on the learning interest of class V students of SDN 127 Inpres Moncongloe?. This study is an experimental study that aims to determine the description of interest, use of media and the influence of the use of learning media on the learning interest of class V students of SDN 127 Inpres Moncongloe, Moncongloe district, Maros regency. The research approach is a quantitative approach. Research data were obtained through tests and questionnaires. The population in the study were all class V students at SDN 127 Inpres Moncongloe, Moncongloe district, Maros regency, totaling 49 students. The sample in the study was 49 students. The data analysis technique was descriptive and inferential statistical analysis. The results obtained in this study are a picture before the use of learning media shows a low category and after the implementation of the use of learning media shows a very high category and interest in learning can be described in the results of the questionnaire obtained, namely in the pretest getting a high score while in the posttest getting a high score and the use of learning media has a significant effect on students' interest in learning, especially in Class V SDN 127 Inpres Moncongloe, Moncongloe District, Maros Regency.